2004
DOI: 10.1007/s11096-004-9007-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the pharmaceutical care needs of asthmatic patients

Abstract: The tool needs further development to ensure its validity and utility in practice. This will provide greater insight into patients' perceptions of their healthcare needs, which can allow health professionals to target their interventions. Such a tool may then be used in pharmacies that intend to change their current practice, to raise pharmacists' awareness of patients' demands. Developing ways to meet those needs will ultimately lead to an increased quality service and therefore 'client' satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…This low rate may also confirm the low interest in participating in pharmacy practices studies found in other recent studies [48, 49]. However, the results from the survey suggest that the potential to develop online services exists.…”
Section: Discussionsupporting
confidence: 83%
“…This low rate may also confirm the low interest in participating in pharmacy practices studies found in other recent studies [48, 49]. However, the results from the survey suggest that the potential to develop online services exists.…”
Section: Discussionsupporting
confidence: 83%
“…First, the sample size (2000 patients, 1000 from each district of Amman) is very good compared with previous similar studies conducted in Jordan (n = 1650) [16] and other countries around the world (n = 100 to 600) [17,18]. This large sample size promotes the generalizability of the findings of this study.…”
Section: Discussionmentioning
confidence: 73%
“…28 In keeping with studies completed in other countries, only a minority of patients received their initial education from nurses and pharmacists. 29,30 Educational approaches, such as the use of multi media and medication information leaflets, have been investigated. 30,31 These approaches should be used to supplement the education provided by health care staff.…”
Section: Education On Inhaler Techniquementioning
confidence: 99%